THE IMPORTANCE OF THE CABIN PRESSURE SYSTEM IN BOEING 737 SERIES - Bintang Rika Wananda; Qorry Khurul Aini; Muhammad Chesa Ramadhan; Hadi Prayitno (Jurnal Penelitian, 2025)
Cabin pressurization is a safety-critical function that enables commercial aircraft to operate efficiently at high cruising altitudes while maintaining a physiologically acceptable environment for passengers and crew. Although the basic functions of aircraft pressurization are widely described, the available literature remains fragmented among environmental control system engineering, aviation medicine, maintenance practices, regulatory requirements, and accident investigation. This study examines cabin pressurization safety in the Boeing 737 family through a structured integrative review and comparative case analysis. Technical publications, international regulations, peer-reviewed studies, maintenance evidence, and official investigation reports published principally between 2005 and July 2026 were examined. The analysis focused on system architecture, regulatory safety limits, failure modes, physiological consequences, crew responses, maintenance factors, and organizational causes. Three official accident cases were comparatively evaluated: Helios Airways Flight 522, Southwest Airlines Flight 812, and Alaska Airlines Flight 1282. A Boeing 737-300F maintenance case study was also used as supporting evidence. The findings demonstrate that pressurization safety does not depend solely on the cabin pressure controller. It results from the interaction of conditioned-air supply, pressure regulation, fuselage structural integrity, warning systems, supplemental oxygen, flight crew response, maintenance configuration control, manufacturing quality, and regulatory oversight. Effective risk reduction therefore requires integrated reliability monitoring, strict restoration of system configuration after maintenance, recurrent decompression training, structural inspection, and the incorporation of pressurization events into operators’ safety management systems.